2010
DOI: 10.1088/1758-5082/2/3/035005
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal neurons respond uniquely to topographies of various sizes and shapes

Abstract: A number of studies have investigated the behavior of neurons on microfabricated topography for the purpose of developing interfaces for use in neural engineering applications. However, there have been few studies simultaneously exploring the effects of topographies having various feature sizes and shapes on axon growth and polarization in the first 24 h. Accordingly, here we investigated the effects of arrays of lines (ridge grooves) and holes of microscale (~2 μm) and nanoscale (~300 nm) dimensions, patterne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 26 publications
3
50
0
Order By: Relevance
“…Nanopatterned surfaces are known to affect cell behavior, such as attachment [8,9], migration [10], and differentiation [11][12][13][14]. Thus, nanopatterns can be used on the surface of an implantable medical device to control cellular activities for different biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Nanopatterned surfaces are known to affect cell behavior, such as attachment [8,9], migration [10], and differentiation [11][12][13][14]. Thus, nanopatterns can be used on the surface of an implantable medical device to control cellular activities for different biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike DRG neurons, Nagata et al showed that central nervous system neuroblasts, including those from the hippocampus, extended neurites primarily perpendicular, but also parallel, to the existing aligned neurite bundles. 42 Later studies extended this to the artificial topographic cues, 43,44 however, parallel hippocampal neurite outgrowth has been reported upon electrospun fibers. 45 DRG and hippocampal neurons provide biomaterial research with two very different neuronal models, representing the two extremes of the neuronal spectrum: a low plasticity peripheral nervous system model that typically does not form networks in culture, and a highly plastic network-forming central nervous system model.…”
mentioning
confidence: 95%
“…In the competitions between the topographies, neurons extended their axons towards the 300 nm lines at a greater frequency than the 2 µm lines, which is consistent with trends reported in the literature showing that smaller lines are more stimulative than larger lines. 14 The competitions between lines and holes indicated that the neurons preferred holes over lines, provided that the different features have an equivalent critical dimension.…”
mentioning
confidence: 99%